Tradisi Neno Bo’ha Dalam Perawatan Masa Nifas: Tantangan Integrasi Budaya dan Kesehatan Modern Di Masyarakat Dawan - Dion, Yohanes; Tahu, Sebastianus Kirniadi; Tanggur, Femberianus Sunario (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The Neno Bo'ha tradition is a form of postpartum care practiced for generations by the Dawan indigenous community. This tradition involves isolation for 40 days in a traditional house (ume kbubu), hot baths (tatobi), body fumigation (se'i), and certain food restrictions. This study aims to examine the dynamics of the existence of the Neno Bo'ha tradition amidst the development of modern health practices, as well as identify challenges and opportunities for integration between the two. The research used a qualitative approach with a case study method. Data were collected through in-depth interviews, focus group discussions (FGDs), observation, and documentation, then analyzed using thematic analysis techniques and source triangulation.Results show that Neno Bo'ha is still strongly practiced because it is believed to protect mothers and babies physically and spiritually. However, this practice presents a number of health challenges such as poor sanitation, infections, nutritional disorders, stunting, and delays in medical access. On the other hand, adaptations have begun to emerge within the community such as the involvement of midwives in care, ritual modification, and health education through traditional leaders. The study concludes that collaborative and culture-based approaches are more effective in increasing community acceptance of modern health practices. Integration of local cultural values with context-sensitive health education is a strategic key to improving the quality of maternal and child care in indigenous areas.